Solar Power Satellites - Flournoy, Don M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Communication satellites are a $144 billion industry. Is there any space-based industry that could possibly beat that market? 'Solar Power Satellites' shows why and how the space satellite industry will soon begin expanding its market from relaying signals to Earth to generating energy in space and delivering it to the ground as electricity. In all industrialized nations, energy demand is growing exponentially. In the developing world, the need for energy is as basic as food and water. The Sun's energy is available everywhere, and it is non-polluting. As business plans demonstrate its technical feasibility, commercial potential, and environmental acceptability, every country on Earth will look to space for the power it needs.
Preface -- Chapter 1: What Is a Solar Power Satellite? -- Chapter 2: What are the Principal SunSat Services and Markets -- Chapter 3: What Will SunSats Look Like? -- Chapter 4: How Will SunSats Be Delivered to Space? -- Chapter 5: How Will SunSat Power Be Captured on Earth? -- Chapter 6: What is the Economic Basis for Solar Power Satellites? -- Chapter 7: What are the Legal Issues? -- Chapter 8: How is SunSat Development Faring Internationally? -- Chapter 9: What is Worrisome about Solar Power Satellites? -- Chapter 10: Top Ten Things to Know About Space Solar Power -- Glossary -- Index.
Keywords: Engineering; Astrophysics; Astronautics; Renewable energy sources; Engineering; Aerospace Technology and Astronautics; Extraterrestrial Physics, Space Sciences; Renewable and Green Energy